Improving Health through Education about Clean and Healthy Living Behavior (CHLB) in The Household - Yulis, Rahma; Wahyuni, Andi; Syam, Ilham; M, Renaldi; Njortetma, Alfredo A (Borneo Community Health Service Journal, 2024)
Perilaku Hidup Bersih dan Sehat (PHBS) or Clean and Healthy Living Behavior (CHLB) is a special program from the Indonesian government. Clean and Healthy Living Behavior must be implemented in all places: in households, educational institutions, workplaces, public places and health service facilities. The aim of this activity is to improve public health through providing education in households. Implementation of this activity consists of four stages: determining the location and time of the activity, preparing material, implementing the activity, and preparation of the activity report. The first stage begins with coordinating the community service team with cadres and village officials. The second stage is the preparation of educational material including: understanding, objectives, benefits, and ten indicators of household CHLB. The third stage provides education using the lecture method on "Clean and Healthy Living Behavior in the household". This activity was held Tuesday, June 6 2023 at the residence of the Village Cadre Chair, in Ta'binjai Hamlet, Lentu Village, Bontoramba District, Jeneponto Regency. The number of participants was 20 participants. At the end of the activity, participants were given a pre-test and post-test to evaluate participants' knowledge. The fourth stage is preparing activity reports which are submitted to village officials. The evaluation results showed that before being given the education, the number of participants classified as having good knowledge was 30.4% of participants and after being given the education the number of participants who were classified as having good knowledge increased to 94.2% of participants.This means that there is an increase in the knowledge of participants who take part in educational activities about CHLB in the household. It is hoped that this knowledge can be transmitted to families and the surrounding community so that the implementation of CHLB in the community can increase.